Multi View Neural Network for Software Effort Estimation Prediction - Setiawan, Boy; Subekti, Agus (Intelligent System and Computation, 2025)
Software Effort Estimation (SEE) is a critical challenge in software project management, dating back to the early years of software engineering. Accurate estimation of the effort required for software development is essential for project planning, resource allocation, and risk management. Incorrect effort estimates can result in poor resource distribution, cost overruns, missed deadlines, and even complete project failure. This issue is increasingly urgent today as software systems are deeply embedded in almost every product and service, amplifying the need for reliable and accurate predictions. Over the years, several methods for SEE have been proposed, ranging from algorithmic models to expert judgment. More recently, machine learning (ML) approaches such as Case-Based Reasoning (CBR), Support Vector Machines (SVM), Decision Trees (DT), and Neural Networks (NN) have gained attention for their ability to model complex, nonlinear relationships inherent in SEE tasks. In this study, we propose a novel approach based on multi-view learning with NN (MVNN), which leverages multiple views from existing datasets, thus improving performance and generalization, particularly when the available data is small and scarce. The effectiveness of the MVNN model is validated through empirical comparisons with existing SEE models, demonstrating its potential to enhance SEE accuracy and improve prediction reliability.